2014
DOI: 10.1159/000362846
|View full text |Cite
|
Sign up to set email alerts
|

Novel, Selective Vitamin D Analog Suppresses Parathyroid Hormone in Uremic Animals and Postmenopausal Women

Abstract: Background: The use of 1α-hydroxylated vitamin D therapy to control secondary hyperparathyroidism in renal failure patients has been a success story, culminating with the demonstration of increased life expectancy in patients treated with these compounds. However, hypercalcemic episodes have been a recurrent problem with these therapies and have resulted in the added use of calcium mimetics. Clearly there is good reason to search for improved vitamin D therapy. In our inventory of vitamin D compounds, 2-methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 62 publications
(53 reference statements)
0
21
0
Order By: Relevance
“…In this study 2MD suppressed serum PTH levels dose-dependently without elevating serum calcium levels at the lowest dose of 220 ng/day. Recently a dose-finding study with 2MD in postmenopausal women confirmed the PTH suppressive effects of 2MD without calcemic side effects (509). A distribution study performed in rats showed that radioactive 2MD was accumulated in the classical target tissues of vitamin D (bone, intestine) but was most strongly localized in the thyroid/parathyroid (509).…”
Section: Vitamin D: Pleiotropic Effectsmentioning
confidence: 98%
“…In this study 2MD suppressed serum PTH levels dose-dependently without elevating serum calcium levels at the lowest dose of 220 ng/day. Recently a dose-finding study with 2MD in postmenopausal women confirmed the PTH suppressive effects of 2MD without calcemic side effects (509). A distribution study performed in rats showed that radioactive 2MD was accumulated in the classical target tissues of vitamin D (bone, intestine) but was most strongly localized in the thyroid/parathyroid (509).…”
Section: Vitamin D: Pleiotropic Effectsmentioning
confidence: 98%
“…31,32 This would suggest that, in the absence of CsA or tacrolimus, 2AMD or 2MD may have a wider therapeutic window. In previous studies, 19,20 2MD was shown to suppress PTH in uremic rats, postmenopausal women, and hemodialysis patients with SHPT. The latter finding was from a dosing trial in which patients received oral 2MD 3 times weekly for 4 weeks and the effective dose range was 330 to 770 ng/dose (or 131-330 ng/day), which is equivalent to 2 to 4.7 ng/kg, assuming patient weight of 70 kg.…”
Section: Discussionmentioning
confidence: 88%
“…The effects of 2AMD at 4 different doses were compared to 2MD at 5 ng/kg in the CsA model, a concentration known to be effective in other measures of renal function. 19,20 Induction of nephrotoxicity was evident in our CsA model, as shown by histologic changes (including increased tubular atrophy and interstitial cellularity) and by significant rises in BUN, increased collagen, fibronectin and vimentin content, and decreased body weight. Testing a range of 2AMD dose regimens allowed us to identify an optimal therapeutic dose and allowed important assessments of the possible effects of a range of relevant doses.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations